MICROSTRUCTURES AND PHYSICAL PROPERTIES OF "BACKFILL" CLAYS: COMPARISON OF RESIDUAL AND SEDIMENTARY MONTMORILLONITE CLAYS - Přikryl R.; Ryndová T.; Boháč J.; Weishauptová Z. (My University, 2003)
Hydrophysical behaviour of a backfill material produced as a mixture of montmorillonite-rich clays (fine-grained fraction) and ballast material (coarse-grained fraction) is studied. Two different genetic types of clays are evaluated—bentonite, representing the residual weathering type, and sedimentary montmorillonite-rich clay. Hydrophysical properties (liquid and plastic limits, permeability and swelling pressure) were determined for mixtures of mixing ratios from 0% to 100% by weight. The microstructural study focused mainly on pore space and specific surface determination that were employed for the interpretation of the hydrophysical properties. The most favourable results were obtained for activated Ca-bentonite but sedimentary montmorillonite-rich clays yielded good quality backfilling mixtures as well. The transition from fine to coarse-fraction dominated behaviour was established for mixtures containing about 20% of clayey admixture.